Analysis of Consigment Sales Rating to 2014 Profit In CV. Lam alif Purwakarta - Gusganda Suria Manda; Dian Hakip Nurdiansyah (BUANA ILMU, 2017)
Abstract The study was conducted with the background, that assessment consignment sales has a direct influence on the financial position of a company and is also considered important because it will indirectly affect the financial statements include a profit and loss. The purpose of this research is to analyze how the results of the calculation of the gain on sale of consignment sales in retail trade company, how a journal to record transactions consignment sales held separately by physical methods, and how the company's ability to generate profits by selling on consignment at CV.LAM ALIF year 2014. Data collection through literature research method, observation, interviews and secondary data from reports of sales and income. The data analysis was descriptive analysis by compiling and classifying the data obtained, then interpreted after the first consignment sales assessment calculation.Results of the study showed that the assessment of the existing consignment sales in retail trade companies (CV. LAM ALIF) for 2014 is quite good, based on the analysis obtained by the profit generated positive accumulated. Judging from the commissions generated that will affect revenue earnings. The conclusion, that the retail trading companies already applying Alif CV.Lam consignment sales. The larger the greater the sales commissions earned by CV. Alif Lam and vice versa if the low sales commissions earned also low. To that end, the need for an increase in consignment sales especially in the bidding. Keyword : Consigment, sales profit, financial